On Some New Types of Fuzzy Soft Compact Spaces - S. Saleh; Tareq M. Al-shami; Abdelwaheb Mhemdi (Journal of Mathematics)
In this article, we apply the concept of fuzzy soft δ-open sets to define new types of compactness in fuzzy soft topological spaces, namely, δ-compactness and δ∗-compactness. We explore some of their basic properties and reveal the relationships between these types and that which are defined by other authors. Also, we show that δ∗-compactness is more general than that which is presented in other papers. To clarify the obtained results and relationships, some illustrative examples are given.